A new Aulacoseira species (Bacillariophyta) from Tierra del Fuego (Argentina) and comparison with the type material of Melosira laevis var. fuegiana Frenguelli. Issue 4 (2nd October 2017) - Casa, Valeria; López Bedogni, Germán; Van de Vijver, Bart
Abstract : A new centric diatom belonging to the genus Aulacoseira was found during a survey of the diatom community from peatbogs of Tierra del Fuego (southern Argentina). The present paper describes Aulacoseira frenguelliana sp. nov. based on detailed light and scanning electron microscopy and compares its morphological features with similar species. Aulacoseira frenguelliana is characterized by short chains joined by spatulate spines, one row of marginal areolae, a very narrow ringleist and only one rimoportula. The type material of Melosira laevis var. fuegiana Frenguelli, a species described from Tierra del Fuego showing some morphological resemblance to the new species, was studied using light microscopy to clarify the taxonomic position of this species. A transfer to Aulacoseira is proposed as A. fuegiana (Frenguelli) comb. et stat nov.